Design, synthesis, and biological evaluation of selective and potent Carbazole-based butyrylcholinesterase inhibitors. Issue 17 (15th September 2018) - Ghobadian, Roshanak; Nadri, Hamid; Moradi, Alireza; Bukhari, Syed Nasir Abbas; Mahdavi, Mohammad; Asadi, Mehdi; Akbarzadeh, Tahmineh; Khaleghzadeh-Ahangar, Hossein; Sharifzadeh, Mohammad; Amini, Mohsen
Graphical abstract: Abstract: Alzheimer's disease (AD) is the most common form of dementia. Inhibition of BChE might be a useful therapeutic target for AD. A new series of Carbazole-Benzyl Pyridine derivatives were designed synthesized and evaluated as butyrylcholinesterase (BChE) inhibitors. In vitro assay revealed that all of the derivatives had selective and potent anti- BChE activities. 3-((9H-Carbazol-9-yl)methyl)-1-(4-chlorobenzyl)pyridin-1-ium chloride (compound 8f ) had the most potent anti-BChE activity (IC50 value = 0.073 μM), the highest BChE selectivity and mixed-type inhibition. Docking study revealed that 8f interacted with the peripheral site, the choline binding site, catalytic site and the acyl pocket of BChE. Physicochemical properties were accurate to Lipinski's rule. In addition, compound 8f demonstrated neuroprotective activity at 10 µM. This compound could also inhibit AChE-induced and self-induced Aβ peptide aggregation at concentration of 100 µM and 10 µM respectively. The in-vivo study showed that compound 8f in 10 mg/kg increased the time spent in target quadrant in the probe day and decreased mean training period scape latency in rats. All results suggest that new sets of potent selective inhibitors of BChE have a therapeutic potential for the treatment of AD.